1996
DOI: 10.1016/0014-5793(96)00230-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide and sequence‐specific DNA damage in human cells

Abstract: Exposure of HeLa cells in monolayer culture to increasing concentrations of exogenously added H202 causes damage to cellular DNA. When the DNA is subsequently isolated from the non-apoptotic cells remaining in such cultures, evidence was obtained to suggest that the DNA damage elicited in intact cells was non-random and that certain nucleotide sequences associated with, or related to, the genes for heat shock protein 60 and catalase were more susceptible to damage than others. In contrast, these particular seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In addition to being generated during cellular metabolism in mitochondria, ROS can be produced in response to different environmental stimuli such as growth factors, inflammatory cytokines, chemical oxidants and chemotherapeutics. Dependent on cell types ROS have been found to function as signaling molecules in cell proliferation and cellular senescence [47], or cell death [48]. The observation of increased autophagy in the brains of patients with AD, PD and HD suggests that autophagy contributes to the pathogenesis of these neurodegenerative diseases; a possible cause is increased cell death [49] because of the constant production of free radicals in mitochondria and changes in the antioxidant system which leads to imbalance, oxidative stress, and neurodegeneration [40].…”
Section: Mitochondria and Redox Stressmentioning
confidence: 99%
“…In addition to being generated during cellular metabolism in mitochondria, ROS can be produced in response to different environmental stimuli such as growth factors, inflammatory cytokines, chemical oxidants and chemotherapeutics. Dependent on cell types ROS have been found to function as signaling molecules in cell proliferation and cellular senescence [47], or cell death [48]. The observation of increased autophagy in the brains of patients with AD, PD and HD suggests that autophagy contributes to the pathogenesis of these neurodegenerative diseases; a possible cause is increased cell death [49] because of the constant production of free radicals in mitochondria and changes in the antioxidant system which leads to imbalance, oxidative stress, and neurodegeneration [40].…”
Section: Mitochondria and Redox Stressmentioning
confidence: 99%
“…Although the sample size of SIDS DNAs used was small it was sufficiently large to detect frequent polymorphisms.5 Importantly, no novel RFLP was detected in the DNAs from infants dying from SIDS. Although no new fragments were revealed, the 6 (table 1). Polymorphisms associated with hsp7O have been reported previously.4 With regard to SIDS, however, the apparent significant association with a polymorphism in the gene encoding hsp60 is novel and of potential importance.…”
mentioning
confidence: 96%
“…In terms of a potential cause it may be relevant that other studies have shown that the loss of the hsp60 15.0 kb MspI fragment also occurs in human cells exposed in vitro to the endogenous oxidant hydrogen peroxide. 6 In terms of function hsp60 itself appears to have an important role in mitochondrial biogenesis,' and impaired mitochondrial function could be a contributory factor in SIDS. Indeed, possible mitochondrial dysfunction in infants dying from SIDS has been observed in the shape of inappropriate brown adipose tissue thermogenesis.7 This alteration of frequency of a polymorphic fragment between SIDS and control DNAs may in the future provide the basis of a test to indicate a predisposition to SIDS, the occurrence of which could be limited by good paediatric care.…”
mentioning
confidence: 99%
“…1993; Dukan and Touati 1996). In cells, ROS can exert either beneficial effects by mediating several physiological processes (Burdon et al. 1996; Finkel and Holbrook 2000; Tomankova et al.…”
Section: Introductionmentioning
confidence: 99%